Kedudukan Visum Et Repertum Dalam Pembuktian Kejahatan Seksual Tanpa Luka - Tiara Intan Camesi; Nola Listi Fitriani; Ria Anggraeni Utami (CV. ITTC INDONESIA, 2026)
This study aims to analyze the legal position of visum et repertum in proving sexual crimes without physical injuries and to examine its role within the criminal justice system. This research employs a normative juridical method using statutory and conceptual approaches, referring to the Kitab Undang-Undang Hukum Acara Pidana and Undang-Undang Nomor 12 Tahun 2022 tentang Tindak Pidana Kekerasan Seksual. The results indicate that visum et repertum serves as both documentary evidence and expert testimony that provides an objective medical description of the victim’s condition. However, in cases of sexual crimes without physical injuries, its evidentiary value is limited as it may not reveal signs of physical violence. Therefore, proof cannot rely solely on visum et repertum but must be supported by other evidence such as victim testimony, witnesses, and circumstantial evidence. This study highlights the importance of a comprehensive and victim-oriented approach to ensure justice in handling sexual crime cases